Keragaman Morfologi dan Genetik Padi Gogo Lokal Asal Banten - Mulyaningsih, Enung Sri; Indrayani, Sri (JURNAL BIOLOGI INDONESIA, 2014)
Superior upland rice cultivar can be assembled through crossbreeding using germplasm diversity which serves as a sourceof gene. Germplasm may constitute of landrace and local cultivars. Banten is one of the provinces that has various localupland rice varieties. Baduy tribe, in the province has played a major role in preserving local upland rice varieties anduphold the wisdom.Genetic diversity information and the benefits of local cultivars can be useful to maximize the selectionprocess of parental candidate for creating new cultivars. This study aims to determine the genetic diversity of local uplandrice from Banten. Methods of analysis diversity performed by phenotypic and genotypic. Observations phenotypic throughobservation of agronomic characters and yield of each cultivar. Whereas genotypic observations conducted with RAPD(random amplified polymorphism DNA). In this study we used 17 local upland rice cultivars from Banten with 14 randomprimers for RAPD. The result showed a mean plant height local upland rice cultivar of Banten was higher than nationalupland rice varieties however productive tillers and rice productivity were lower than national varieties. Nonetheless, localcultivars persisted in this environment because it has the advantage that the community needed. Based on the time ofharvest, local cultivar belonged to early and medium maturing group. Qualitative trait observation showed that there werediversity of stem, leaves, grain and rice among the cultivars. Genetic analysis with RAPD showed nine primers out of 14were successful in amplifying loci from DNA template. The primers having high amplification product were OPJ 05, OPJ07 and OPD07 but the highest polymorphism presentation was OPJ 01. Based on phylogenetic tree, there were two mainclusters. Padi Koneng and Carogol were similar. Three glutinous rice cultivars (Mayang, Jalupang, and Hideung) were inone cluster except Kentan Simpai.Keywords: upland rice, Banten, RAPD, Phenotipe, genotype